Parceria ou mera relação social? Estudo de Caso das relações entre a BASF SA e a comunidade do seu entorno em Guaratinguetá/SP - Bonventti, Rodolfo Carlos (2013)
Study about the communication relations between the BASF multinational and the community in around the city Guaratinguetá, in the interior of São Paulo. The general objective is going to analyze in that conditions a multinational company and a community to his around can fix in the practical one a partnership in search of a management socially more responsible, as well like verify which the power of interference of that community in his trials of communication. The methodology utilized was a case study by means of analysis of documents, observation participant in meeting of the Communal Advice, group of argument and interviews, beyond bibliographical research. We are going to understand the perception of members of the Advice, of inhabitants of the city, of the local media and also of the communication professionals from multinational. To main conclusion is that what would be able to be constituted in a partnership of success for both the sides, finishes itself restraining to a mere social relation, where the two sides look feel well and are guilty of that carry out his works of the best possible way.